(untitled) (Journal of Health, Population and Nutrition, 2010)
Multidrug-resistant tuberculosis (MDR-TB) has been a cause of concern in both developed and developing countries. The prevalence of drug resistance in Mycobacterium tuberculosis (MTB) isolates (n=692) from Mpumalanga province was assessed. In total, 692 (64%) MTB strains from cases with pulmonary TB were tested for susceptibility against rifampicin, isoniazid, ethambutol, and streptomycin using the MGIT 960 instrument. Two hundred and nine (30.2%) strains were resistant to one or more drugs. Resistance to one drug ranged from 1.4% for ethambutol to 17.7% for rifampicin. The prevalence of MDR-TB ranged from 6.7% for three drugs to 34% for four drugs, with significant predictors being patients’ age-groups of 25-54 years (p=0.0012) and >55 years (p=0.007). The result showed a high level (58.4%) of MDR-TB from cases in Mpumalanga province. To achieve a higher cure rate in this province, drug-susceptibility tests must be done for every case. Key words: Drug resistance; Microbial; Mycobacterium tuberculosis; Risk factors; Tuberculosis; South Africa DOI: 10.3329/jhpn.v28i1.4518 J Health Popul Nutr 2010 Feb; 28(1): 7-13